Investigation into methods for the calculation and measurement of pulverised coal boiler flue gas furnace exit temperature - Tootla, Naeem Ebrahim (Department of Mechanical Engineering, 2016)
The boiler flue gas furnace exit temperature (FET) is a key operating parameter of coal fired steam boilers. From the design perspective, the FET is vital for materials selection and sizing of heat transfer surfaces. From an operating perspective, it is a major indicator of the rate of combustion and heat transfer that is occurring within the furnace. Downstream of the furnace, the FET has a significant impact on both the performance and reliability of the boiler heat exchangers, which ultimately impacts on both boiler efficiency and availability. Monitoring of the FET can advise operating and engineering corrective actions which will ultimately result in better efficiency, reliability and availability together with the associated economic benefits. Therefore, methods of determining FET are investigated. Two methods are focused on for this study, one indirect and one direct. The indirect method studied is a mass and energy balance method which begins with a global boiler mass and energy balance to calculate the major boiler flow rates of coal, air and flue gas which are difficult to measure online. These parameters are then used as inputs into a furnace or backpass mass and energy balance to calculate the furnace exit temperature. The method is applied to a case study, and is evaluated in terms of the measurement uncertainties which are propagated on the intermediate parameters calculated, as well as on the final calculated FET. The main conclusions are that this indirect method contains various uncertainties, due to parameters which have to be assumed such as (i) the distribution of ingress air (also called tramp air) in the different sections of the boiler and (ii) the estimation of the share of water evaporation heat transfer occurring in the water walls of the furnace part of the boiler. The method is however still useful and can be easily applied to any boiler layout and can be used as a reference tool to verify other measurements. The direct method studied is acoustic pyrometry. The work specifically focuses on the sources of error in determining the temperature from the measurement of the time of flight of sound, the impact of particle concentration on the speed of sound through a gas-particle mixture, and the temperature profile reconstruction from acoustic time of flight measurements. A limited set of physical testing was also carried out using one acoustic generator and receiver to take measurements on a real coal power plant. As part of this physical testing, the detection of time of flight from acoustic signals was explored. Already installed radiation pyrometers were also used as a reference for interpreting the acoustic measurements. The indications are that the acoustic pyrometer provides a more representative temperature measurement than the radiation pyrometers. The uncertainty of the acoustic measurement for the same case study as the indirect method was determined and compared with the calculated result. While many aspects still need to be researched further, this initial study and experimental testing produced very promising results for future application of acoustic pyrometry for better monitoring of the coal combustion processes in power plant boilers.